1998
DOI: 10.1101/lm.4.5.401
|View full text |Cite
|
Sign up to set email alerts
|

Two critical periods of protein and glycoprotein synthesis in memory consolidation for visual categorization learning in chicks.

Abstract: A protein synthesis inhibitor, anisomycin (ANI), and an inhibitor of glycoprotein synthesis, 2-deoxygalactose (2-D-gal), were used to investigate memory consolidation following visual categorization training in 2-day-old chicks. ANI (0.6 pmole/chick) and 2-D-gal (40 lamoles/chick) were injected intracerebrally at different time intervals from 1 hr before to 23 hr after the training. Retention was tested 24 hr post-training. Both ANI and 2-D-gal injections revealed two periods of memory sensitivity to pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 39 publications
3
33
0
1
Order By: Relevance
“…This is consistent with several previous studies that have repeatedly demonstrated that inhibition of protein synthesis 6 h or longer following training (in the absence of a recall trial) does not disrupt memory consolidation of the training event (Squire et al, 1975;Tiunova et al, 1998;Nader et al, 2000). Therefore, it is unlikely that inhibition of hippocampal protein synthesis 24 h following the two-training session protocol interferes with consolidation of the original training event, but that its effect was as a result of the reactivation of this robust memory.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with several previous studies that have repeatedly demonstrated that inhibition of protein synthesis 6 h or longer following training (in the absence of a recall trial) does not disrupt memory consolidation of the training event (Squire et al, 1975;Tiunova et al, 1998;Nader et al, 2000). Therefore, it is unlikely that inhibition of hippocampal protein synthesis 24 h following the two-training session protocol interferes with consolidation of the original training event, but that its effect was as a result of the reactivation of this robust memory.…”
Section: Discussionsupporting
confidence: 90%
“…Galactose is incorporated into complex oligosaccharides of membrane and secretory glycoproteins in the Golgi, but galactose and some of its derivatives can also be added to proteins in the cytosol as transient or permanent posttranslational modifications (14). The galactose-containing disaccharide, fucose-␣(1-2)galactose, has been implicated in memory formation, learning, and synaptic plasticity (15)(16)(17)(18)(19)(20)(21). Fucose-␣(1-2)galactose sugars are enriched on glycoproteins in presynaptic nerve terminals (22), and it has been shown that fucose-␣(1-2)-galactose modification has profound effects on the expression and degradation of the synaptic vesicle-associated protein, synapsin (22).…”
Section: Discussionmentioning
confidence: 99%
“…Cherkin (1969) developed a one-trial passive avoidance learning task based on the young chick's tendency to peck at small bright objects such as beads, which is discussed in more detail below. In an appetitive visual discrimination task, the chick learns to distinguish food crumbs scattered on the floor of its pen from rather similar pebbles or beads glued to the surface (Andrew and Rogers 1972;Tiunova et al 1998). Isolated chicks will quickly learn a simple maze to rejoin their hatchmates (Gilbert et al 1989;Regolin and Rose 1999).…”
Section: Learning Paradigmsmentioning
confidence: 99%